A Comparative study of solidification of Al-Cu alloy under flow of cylindrical radial heat and the unidirectional vertically - Rodrigues, Jean Robert P.; Mello, Mírian de Lurdes N. M.; Eid, Marco Antonio; Nevez, Tiago do E. S. B.; Araujo Junior, Antonio S; Rodrigues, José R. P. (Acta Scientiarum. Technology, 2014)
In spite of technological importance of solidification of metallic alloys under radial heat flow, relatively few studies have been carried out in this area. In this work the solidification of Al 4.5 wt% Cu cylinders against a steel massive mold is analyzed and compared with unidirectional solidification against a cooled mold. Initially temperature variations at different positions in the casting and in the mold were measured during solidification using a data acquisition system. These temperature variations were introduced in a numerical method in order to determine the variation of heat transfer coefficient at metal/mold interface by inverse method. The primary and secondary dendrite arm spacing variations were measured through optical microscopy. Comparisons carried out between experimental and numerical data showed that the numerical method describes well the solidification processes under radial heat flux. Â